Effects of heat and cold shock-induced triploidy on productive parameters of silver catfish (Rhamdia quelen) late-hatched in the reproductive season - Morón Alcain, Esteban (2017)
This study was carried out in order to assess the productive performance of triploids of silver catfish (Rhamdia quelen) obtained by heat (HT) and cold shock (CT) at the end of the reproductive season. In hatchery, HT larvae reached the highest survival rate since they exhibited the lowest cannibalism rate among all groups. Although mean weight of larvae in HT group was lower in comparison with CT and diploid counterparts, the final biomass of HT was the highest due to the great survival rate observed in this group. At the end of the fattening trial both HT and CT groups showed better productive parameters than diploid control group. The mean weight of HT and CT were significantly higher than diploids. The condition factor was significantly higher in HT in comparison with CT and diploid fish. However, only CT males and females showed significantly higher carcass weight than control fish. Also carcass yield was greater in triploid females although only CT males displayed significantly higher carcass yield than their diploid counterparts. The gonadosomatic index (GSI) exhibited a different pattern in each sex. In males, CT showed a significantly lower GSI in comparison with HT and diploid fish. Control females displayed the highest GSI with significant differences with both triploid groups. In addition, CT males and females accumulated significantly higher percentage of abdominal fat than their control counterparts. A strong negative correlation between GSI and carcass yield in females was observed. These results demonstrate that HT and CT of R. quelen exhibited superior productive parameters than control fish in both hatchery and fattening period. Since some variables assessed were better in HT while others were improved in CT group, the election of heat or cold shock-induced triploids for culture should be based on the productive aims of each fish farm.